Modelamiento de una turbina eólica Darrieus h de eje vertical implementando el método de Sliding Mesh por simulación CFD (2019)
This project was born with the requirement to identify the power curves of a Darrieus H wind turbine, by means of modeling in CFD tools (“Computational Fluid Dynamic”), using a transient state method known as Sliding Mesh. Using operating conditions of a selected area in Colombia, determining the input parameters for the modeling and simulation stages. Different discretization methods are used that be able to corroborate the results achieved by the main method of study and finally validate the information obtained by the procedures performed in the Sliding Mesh model with references from other authors.